Reunión. (UNED, 2024)
Reunión del Consejo Universitario, en el edificio B. De izquierda a derecha: Carlos Hernández Orozco, Francisco Montero González y Celedonio Ramírez Ramírez; atrás Ana Isabel Tristán Sánchez, Fulvio Fonseca Hernández, de pie Florencio Magallón Molina